'Barbarian Sages' between Christianity and Paganism in Ammianus Marcellinus and the Cosmographia Aethici - Lampinen, Antti (Helsinki University Press, 2025)
The chapter compares the representation of 'sages', 'philosophers' or 'wise men' in Ammianus Marcellinus' Res Gestae from the late 4th century and in the Cosmographia Aethici of 'Pseudo-Jerome' from the 8th century, with a particular focus on the ways in which these two widely differing texts engage with the idea of 'pagan' or 'barbarian' wisdom traditions and their carriers. In so doing, the chapter compares the two authors' strategies and techniques in representing inherited, non-Greek (or non-Roman) wisdom among the peoples of the world. Despite the great differences between the two texts and the contexts of their creation, both surprising similarities and telling differences can be found between them. Both texts love to refer to secret letters and hidden information; another similarity is the way both authors tried to avoid locking themselves into either a 'Christian' or a 'pagan' way of writing. The resulting complications are in both cases part of the author's reflection on the difficulty of extracting truth from testimonies with various degrees of authority and age.
BEING PAGAN, BEING CHRISTIAN IN LATE ANTIQUITY AND EARLY MIDDLE AGES